ANALYSIS OF MSME DEVELOPMENT THROUGH E-COMMERCE REVIEW OF MAQASID SYARIAH (CASE STUDY IN MEDAN CITY) - Salsabila, Rofilla; ,., Nurbaiti; Tambunan, Khairina (LPPM Universitas Trunojoyo Madura, 2025)
This study aims to analyze the development of Micro, Small, and Medium Enterprises (MSMEs) through e-commerce in the context of maqasid syariah, with a case study in the city of Medan. The study employs a qualitative method, with the research location in the city of Medan. The findings indicate that e-commerce significantly contributes to the development of MSMEs, particularly in developing MSMEs on e-commerce platforms that align with the principles of maqasid syariah. Some challenges faced by MSMEs in adopting e-commerce include limited digital literacy, inadequate technological infrastructure, insufficient capital, and intense competition in the online market. Therefore, future research could address these limitations by expanding the sample size and research area, as well as conducting a more in-depth examination of effective e-commerce strategies and business models for MSMEs.Keywords: MSMEs, E-Commerce, Business Development, Maqasid Syariah, Medan